Run for the hills, Geronimo! - STILTON, GERONIMO (New York Scholastic Inc, 2009)
In Run for the Hills, Geronimo! (#47), Geronimo Stilton plans a relaxing solo vacation, but his family surprises him, turning it into a chaotic treasure hunt in South Dakota's Black Hills.
English